MINI REVIEW: PENERAPAN BERBAGAI IONOFOR DALAM PEMBUATAN ELEKTRODA SELEKTIF ION (ESI) Pb2+ SECARA POTENSIOMETRI - Padang, Dea Angelina Tiku; Yusuf, Bohari; Arif, Moh Syaiful (PROSIDING SEMINAR KIMIA, 2024)
This mini review provides a brief overview of the application of various types of ionophores in the fabrication of ion-selective electrodes (ISE) for detecting Pb2+ ions using the potentiometric method. Ionophores are key components in ISEs that determine the selectivity and sensitivity of the electrode toward the target ion. The purpose of this review is to provide insights into selecting effective ionophores for potentiometric applications in detecting Pb2+ contamination in the environment. The method used in this review involves screening articles on google scholar, research gate, and garuda published between 2015 and 2022. In this review, five types of ionophores were identified as active membrane materials for the fabrication of Pb2+ ISEs, including chitosan; 1,10-dibenzyl-1,10-diaza-18-crown-6 with anionic site KTCPB; dithizone; 1,10-diaza-18-crown-6 with anionic site KTCPB; and pt-butylcalix[4]arena with anionic site KTCPB. These ionophores were found to have Nernst values of 29.1, 29.64, 29.5, 27.61, 26.15, and 27.61 mV/decade, respectively. Dithizone was identified as the most effective ionophore for detecting Pb2+ due to its Nernst value being closest to the theoretical Nernst value of 29.57 mV/decade. Keywords: Ion-Selective Electrode (ISEs), ionophores, potentiometry, Pb2+ ions, Nernst factor